Metabolic Control of Cell Elongation and Cell Division in Bacillus subtilis - Galinier, Anne; Foulquier, Elodie; Pompeo, Frédérique (Frontiers in Microbiology, 2021)
To survive and adapt to changing nutritional conditions, bacteria must rapidly modulate cell cycle processes, such as doubling time or cell size. Recent data have revealed that cellular metabolism is a central regulator of bacterial cell cycle. Indeed, proteins that can sense precursors or metabolites or moonlighting proteins, in addition to their enzymatic activities involved in metabolism, were shown to directly control cell cycle processes in response to changes in nutrient levels. Here we focus on cell elongation and cell division in the gram-positive rod shape bacterium Bacillus subtilis and we report evidences linking these two cellular processes to environmental nutritional availability and thus metabolic cellular status.